Engineering mechanics: Statistic & Dynamics - Francesco, Costanzo (McGraw-Hill, 2010)
This book emphasizes critical thinking by presenting the reader with engineering situations. Compelling photorealistic art, and a robust photograph program helps readers to connect visually to the topics discussed.